(untitled) (Research, Society and Development, 2020)
The federal institutes stand out in promoting the instruction, research and extension; and the research groups represent an important role to promote and scatter the scientific knowledge. In that way, the research groups of the Federal Institute of Education, Science and Technology of Mato Grosso (IFMT), which is the object of study of the following paper, represent an important contribution for the research as an educational principle. Therefore, this article aims to analyses the publications of the registered participants as researchers of the IFMT research groups, linked to the campus Cuiabá-Cel. Octayde Jorge da Silva, and identify the record of their publications in the Lattes Platform. By analyzing the history of the scientific papers of the mentioned groups above, it is expected to embrace how knowledge is produced and deepened thanks to their work. To do so, the time period was delimited to span the publications from 2018 to 2020 for all participants in the Lattes Platform. The methodology adopted for this descriptive and quantitative research, the use of bibliographic and documentary data collection was applied. As main results achieved, it stands out the evidence demonstrated that the research groups analyzed have an active play role, it was identified the predominant areas in the research groups, the collaboration of its members in research projects, like the type of publications developed by its members and the records in the Lattes Platform. In this way, it was highlighted the importance of research groups in the broadcast and socialization of scientific knowledge, characterizing them like relevant tools in the educational processes developed by the Federal government.